2017
DOI: 10.1186/s12943-017-0639-2
|View full text |Cite
|
Sign up to set email alerts
|

DC - SIGNR by influencing the lncRNA HNRNPKP2 upregulates the expression of CXCR4 in gastric cancer liver metastasis

Abstract: BackgroundProfiling evidences of selectin demonstrate that they play an crucial role in cancer progression and metastasis. However, DC-SIGNR as a family member of selectin participates in gastric cancer liver metastasis remains unknown.MethodsThe serum level of DC-SIGNR was evaluated in gastric cancer patients by ELISA. Manipulation DC-SIGNR expression in BGC823 and SGC7901 cell lines was mediated by lentivirus. Investigation the biological effects of DC-SIGNR were verified by MTT, wounding and transwell in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
2
32
2
Order By: Relevance
“…For example, the binding of EZH2 to lncRNA (AGAP2‐AS1) in GC promotes the invasion of GC cells via binding enhancers of zeste homolog 2 (EZH2) while suppressing E‐cadherin . HNRNPKP2 contributes to the progression of GC, which serves as an indicator of poor prognosis . Additionally, the elevated AK023391 is related to poor prognosis of GC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the binding of EZH2 to lncRNA (AGAP2‐AS1) in GC promotes the invasion of GC cells via binding enhancers of zeste homolog 2 (EZH2) while suppressing E‐cadherin . HNRNPKP2 contributes to the progression of GC, which serves as an indicator of poor prognosis . Additionally, the elevated AK023391 is related to poor prognosis of GC .…”
Section: Discussionmentioning
confidence: 99%
“…12 HNRNPKP2 contributes to the progression of GC, which serves as an indicator of poor prognosis. 13 Additionally, the elevated AK023391 is related to poor prognosis of GC. 14 Here in our investigation, the biological role of LOC285194 in GC was elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CLEC18B expression was significantly altered in glioblastoma multiforme tissue, and was identified as an independent predictor of patient survival (10). Additionally, it has been demonstrated that selectin influences the progression of numerous cancer types, including colon carcinoma (11,12) and gastric cancer (13). Coupland et al (14) discovered that P-selectin promoted the lung metastasis of breast cancer and melanoma in vivo.…”
Section: High Expression Levels Of Clec4m Indicate Poor Prognosis In mentioning
confidence: 99%
“…For example, CLEC4M is associated with poor prognosis in patients with colon cancer, and it is involved in the adhesion, migration, invasion and liver metastasis of colon cancer cells (21). Furthermore, CLEC4M exerts these biological functions through the signal transducer and activator of transcription 5/long non-coding RNA Heterogeneous Nuclear Ribonucleoprotein K Pseudogene 2/ C-X-C chemokine receptor type 4 axis (13). Although CLEC4M has been examined in several malignant tumor types, to our knowledge, the clinical significance of CLEC4M has never been investigated in HCC so far.…”
Section: High Expression Levels Of Clec4m Indicate Poor Prognosis In mentioning
confidence: 99%
“…Abnormal expression and regulation of lncRNAs were involved in oncogenesis and development, including GC. PVT1, HNRNPKP2, HOXA11-AS and many other lncRNAs can affect the malignant phenotype of GC cells at transcriptional and post-transcriptional levels [7][8][9]. In 2015, lncRNA Downregulated RNA in cancer (DRAIC) was firstly reported as a target gene of FOXA1 and NKX3-1 to inhibit the ability of transition from an androgendependent (AD) to a castration-resistance state, epithelial-mesenchymal transition (EMT) and metastasis of prostate cancer cells, and TCGA database analysis showed that its expression was closely related to the survival rate of patients with malignant tumors such as GC, lung cancer and hepatocellular carcinoma [10,11].…”
Section: Introductionmentioning
confidence: 99%